To Share or Not to Share? The Role of Retailer’s Information Sharing in a Closed-Loop Supply Chain - Zhang, Huaige; Hong, Xianpei; Cao, Xinlu (Frontiers in Psychology, 2022)
Retailers are faced with a dilemma of whether to share demand information to other supply chain members, and if so, how to share it. Our research interest is motivated by the grounds that the value of downstream retailers' sales information to upstream manufacturers is to improve the accuracy of manufacturers' order forecasting. This problem is particularly important in a remanufacturing closed-loop supply chain (CLSC). In this study, we consider a retailer (she), as the demand information holder, who sells new and remanufactured products wholesale from a manufacturer (he) and, simultaneously, she and the manufacturer competitively collect used products from the customers. We explicitly characterize what is the role of the information sharing in a CLSC. We make a contribution to the information sharing literature by integrating the existing information sharing model with dual recycling channels and channel power structure. Previous literature suggests that retailers prefer to share demand information to other firms when the market demand is high. However, surprisingly, we find that when the manufacturer does not play a leading role, the retailer shares her forecast demand information with the manufacturer iff the market demand is low. We also show that information sharing reduces the overall profit of the supply chain when the manufacturer dominates the market. In addition, we our results also illustrate that information sharing affects the performance of supply chain mainly by affecting the wholesale price.